DIACHRONIC STUDY OF THE VARIABILITY AND SICKNESS ABSENTEEISM AND PRESENTEEISM FACTORS : THE CASE OF THE PRODUCTION UNIT OF LUXURY SECTOR COMPANY’S - Marc DUMAS (Revue de Gestion des Ressources Humaines, 2013)
research on sickness absenteeism extended recently in the understanding of presenteeism and presenteeism and absenteeism relations. The object of the study is to test 8 hypotheses relating to these two phenomena. The methodology is mixed, qualitative and quantitative. The data of sick leave of a population of 278 employees of production of 2 factories are studied over a period of 6 years. 103 interviews with “absent” employees and “presents” were led. Our results tend to show that the absenteeism is more connected to the organizational context than to the employment or personal factors. The historic level of absenteeism, more than the variations, explains the absenteeism. Besides concerning the presenteeism, in a general context of increase of the absenteeism, both phenomena coexist. The reactive practices against the absenteeism implemented by companies can explain the presenteeism